Adolescent girls and young women living with HIV: preconception counseling strategies - Jones DL; Echenique M; Potter J; Rodriguez VJ; Weiss SM; Fischl MA (Dove Medical Press, 2017)
Deborah L Jones,1 Marisa Echenique,1 JoNell Potter,2 Violeta J Rodriguez,1 Stephen M Weiss,1 Margaret A Fischl3 1Department of Psychiatry and Behavioral Sciences, 2Department of Obstetrics and Gynecology, 3Department of Medicine, Division of Infectious Diseases, University of Miami Miller School of Medicine, Miami, FL, USA Background: Rates of pregnancy among women living with HIV are similar to those in the general population. Unintended pregnancies are also common, and among adolescents and young women perinatally infected (PHIV+) or behaviorally infected (BHIV+) with HIV, planning for both conception and contraception is an important element of HIV care that may be neglected. This pilot study examined the influence of intervention strategies targeting fertility planning, safer conception practices and patient-provider communication. It was hypothesized that preconception counseling interventions would enhance reproductive knowledge, planning and practices, as well as stimulate discussion with providers regarding conception. Methods: Adolescent girls and young women (N=34) perinatally (n=21) or behaviorally (n=13) infected with HIV, aged 16–29 years, were recruited from urban South Florida, and completed measures of reproductive knowledge, sexual practices and fertility intentions. Participants were randomized to condition, ie, video presentation plus Motivational Interviewing (MI), MI only, control. Results: The average age of women was 22 years (SD =3.27), and the majority of them were African American. Levels of depression were higher among BHIV+ compared to PHIV+ at baseline and 6 months. Pregnancy knowledge (pregnancy, safe conception and pregnancy planning) and the proportion of those engaging in birth control planning (condom use, long-term birth control, patient-provider discussions on preventing pregnancy and fertility desires) were similar between conditions at post-intervention and 6 months. Bayes factors indicated that the data were insensitive with regard to differences between conditions, limiting support for both the null and alternative hypotheses. Conclusion: The impact of interventions used in this study to stimulate pregnancy planning was inconclusive. Results suggest that pregnancy planning interventions may require greater intensity to influence sexual behavior in this population. Despite adequate reproductive knowledge, HIV-infected adolescent girls and young women may fail to engage in planning behavior. Keywords: adolescents, young women, HIV, reproduction, family planning, safer conception, preconception counseling